La necesidad de implementar como requisito en los procedimientos sumarios de patria potestad y tenencia, informe valorativo psicológico de los progenitores - Robles Romero, Gilda Jhulissa (2024)
This research delves into the intersection between the legal field and the psychological well-being of minors in situations of separation or divorce. Through an exhaustive analysis supported by results from surveys, interviews and detailed analysis, the study defends the importance of incorporating psychological evaluative reports as a requirement in judicial custody and custody proceedings.The introduction sets the context by highlighting the growing relevance of this topic, which addresses the intersection between the legal and emotional spheres of the minors involved. In the effort to guarantee the protection and well-being of minors in complex legal circumstances, the research proposes the inclusion of psychological assessment reports as an essential resource. The outlined objectives provide the conceptual framework of the research, focused on demonstrating the relevance of psychological evaluation in making judicial decisions related to parental authority and possession. The proposed hypothesis reinforces the idea that the lack of psychological evaluation of the parent who is the beneficiary of custody could result in the violation of the right to a dignified family life, thus affecting the adequate development of the minors. The conclusions drawn emphasize the coherence and consistency of the findings, strengthening the idea of introducing psychological evaluative reports as a means to safeguard the best interests of minors and promote their comprehensive well-being. However, potential challenges are also highlighted, such as increased costs and additional burden on courts, as well as the need to ensure the quality and impartiality of reporting.